Effects of fecal microbiota transplantation on glycemic and lipid profiles in overweight or obese patients with metabolic disorders: a systematic review and meta-analysis - Zhang, Yuxin; Cao, Jingsi; Wang, Yanyan; Fan, Xuechun; Deng, Ruixue; Mi, Jia (Frontiers in Endocrinology, 2025)
Obesity and its associated metabolic disorders (such as type 2 diabetes, metabolic syndrome, and NAFLD/MASLD) represent a global health challenge. Fecal microbiota transplantation (FMT), as a therapy regulating the gut microbiome, has demonstrated inconsistent clinical efficacy. This systematic review aims to evaluate the impact of FMT on key indicators of glucose and lipid metabolism in overweight/obese adults with metabolic diseases. We systematically searched PubMed, Embase, Cochrane, and Web of Science databases up to September 28, 2025, to identify randomized controlled trials evaluating FMT for obesity and metabolic disorders. Data were pooled using a random-effects model, with primary outcomes being changes in BMI, HOMA-IR, and HbA1c relative to baseline. A total of 11 RCTs (320 participants) were included. The primary analysis showed that FMT intervention demonstrated a trend toward improvement in the primary outcome measures, BMI (MD: -0.65, p = 0.070) and HOMA-IR (MD: -0.64, p = 0.062), but these trends did not reach statistical significance. There was no significant effect on HbA1c (MD: 0.06, p = 0.742). However, this negative conclusion based on the conventional assumption (Corr = 0.5) exhibited high instability: sensitivity analysis revealed that FMT’s improvement effects on BMI became statistically significant (p = 0.010) when the correlation coefficient (Corr) used to estimate the standard deviation of change was adjusted to 0.75. Furthermore, meta-regression analysis revealed that treatment regimen, follow-up duration, and patient baseline characteristics were significantly associated with HbA1c efficacy. Based on the current “low” certainty evidence, the overall improvement of metabolic parameters in overweight or obese patients with metabolic diseases following FMT did not reach statistical significance in the primary analysis. However, the robustness of this negative finding is limited, exhibiting high sensitivity to statistical hypotheses and likely being significantly confounded by methodological factors (e.g., administration protocols) and donor variability. Consequently, the true efficacy of FMT for treating systemic metabolic disorders remains uncertain. Future trials should shift toward precision medicine, prioritizing the standardization of donor selection and optimization of administration protocols.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD420251172011, identifier CRD420251172011.